A new animal model for menopausal transition: combination of ovariectomy and empty bottle stimulation. (3rd October 2018) - Ye, Yang; Liu, Cun-Zhi; Wang, Rui; Zhang, Yu-Wei; Zhang, Bo; Cui, Yu; Liu, Xue-Wei; Huang, Shu-Ming
Abstract: Previous small animal models for menopausal transition are mainly performed to mimic the biochemical changes of patients with menopausal transition. The psychological symptoms in animal models are often overlooked. To mimic clinical situation, we developed a new mouse model of menopausal transition: the combination of bilateral ovariectomy (OVX) and empty bottle stimulation (EBS). After OVX and 21 days of EBS, behavioral test and pentobarbital-induced sleep test were carried out. Then all the animals were euthanized for further investigations. Compared with the control group, the combination of OVX and EBS group (OVX + EBS) showed higher bodyweight, lower organ index of uteri, and lower concentrations of serum estradiol. In addition, behavioral manifestations, sleep quality, and morphologic features in OVX + EBS group showed significant differences compared with the control group. OVX alone or EBS alone failed to include all the changes of OVX + EBS group. These findings indicate ovariectomy or EBS alone could not well mimic the symptoms of menopausal transition. The combination of bilateral ovariectomy and EBS offers an easy and repeatable method for building comprehensive menopausal transition model in mice.